O ensino da matemática nos anos iniciais: uma abordagem a partir de um tema gerador - Costa, Jaqueline de Morais (2011)
This study had as an objective to investigate how the proposed teaching through Theme Generators can contribute to teaching and learning of mathematics in the early years of elementary school. The research was conducted with students in 3rd year of 1st cycle of basic education in a school of the Municipal Education of the city of Ponta Grossa, Parana. In order to create strategies that would meet the training needs of students, it was chosen the adoption of a generative theme to develop the curriculum contents in mathematics. The directing, collecting and analyzing data were produced by the interpretative research, of qualitative nature with its purpose applied. During the development of the activities, it was realized greater involvement of the students with the contents whether compared to the strategies of earlier work, as well as it was also noticed the progress in learning, shown through formative assessment by using different tools. Based on the developed work it was carried out a textbook on interactive in DVD, whose goal is to provide teachers of early years a working script to develop the contents of mathematics in a contextualized way, using generative themes.